PENGENDALIAN BEBAN GENERATOR SECARA OTOMATIS DENGAN ALGORITMA PID PADA PLTMH BERBASIS PLC - - Hardiansyah; Eka Firmansyah; M Isnaeni BS (MEDIA ELEKTRIKA, 2012)
Micro hydro power system (PLTMh) is a plant thai utilizes water flow. To stabilize the flow of electricity produced by the generator it is necessary to control the use of the load on the generator. PLTMh currently only using electronic devices to controls the lood have some weakness such as monitoring of the PLTMh to be done is directly and continuously so it will cost and effort very much. This research aims to control the PLTMH automatically using Programmable Logic Controller (PLC) twido TWDLMDA 20 DRT using the algorithm Proportional Integral Derivative (PID) and can allow remote monitoring of the PLTMH in combination with Supervisory Control and data Acquisition (SCADA). By wing the PLC controlling the generator can be stabilized on the circumstances we want is at a voltage of 220 volts with a frequency of 50 Hz.Keyword: PLTMH